Analisis Pola Pembelian Suku Cadang dengan Algoritma FP-Growth dan Visualisasi Data Penjualan - Hendry, Tivelin; Mardiani, Mardiani (Universitas Multi Data Palembang, 2025)
PT Indo Global Cemerlang faces challenges in identifying customer purchasing patterns, which impacts marketing strategies and inventory management. This research aims to analyze purchasing patterns using the FP-Growth algorithm and present the results in a data visualization dashboard. Transaction data for the period August-October 2024 was processed using the CRISP-DM approach, including business understanding, data preparation, modeling, evaluation, and deployment. The FP-Growth algorithm was applied with a minimum support of 0.003 and confidence of 0.6, resulting in 24 association rules visualized in an interactive dashboard. The test results show that this method is effective in identifying purchasing patterns, and the dashboard developed is able to present information comprehensively and easily interpreted, thus supporting business decision making.